2007
DOI: 10.1021/ja0710306
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Polymer Brushes of Regioregular Head-to-Tail Poly(3-alkylthiophenes) via Catalyst-Transfer Surface-Initiated Polycondensation

Abstract: We describe a new method to grow conductive polymer (CP) brushes of regioregular head-to-tail poly(3-alkylthiophenes) (P3AT) via surface-initiated polycondensation of 2-bromo-5-chloromagnesio-3-alkylthiophene. A simple procedure for the preparation of the Ni(II) macroinitiator by the reaction of Ni(PPh3)4 with photocross-linked poly-4-bromostyrene films was developed. Exposure of the initiator layers to the monomer solution leads to selective chain growth polycondensation of the monomer from the surface, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
229
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(247 citation statements)
references
References 28 publications
12
229
2
3
Order By: Relevance
“…[65] Doubina et al [70] used the air-stable 3 have shown a much worse performance than bidentate ligands such as dppp or dppe, which was ascribed to extensive chaintermination and reinitiation reactions. [43,44] An one-pot preparation of Ni-initiators supported by bidentate ligands was attempted by Doubina et al Nickel cyclooctadiene (Ni(cod) 2 ) was reacted with aryl halides followed by the addition of one equivalent of a bidentate ligand (dppf, dppe, or dppp), or of two equivalents of the monodentate ligand PPh 3 (Scheme 3c). [71] The idea was to utilize the high reactivity of Ni(cod) 2 toward aryl halides combined with the lower binding ability of cod to nickel compared to bidentate phosphorous ligands.…”
Section: Ex Situ (External) Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…[65] Doubina et al [70] used the air-stable 3 have shown a much worse performance than bidentate ligands such as dppp or dppe, which was ascribed to extensive chaintermination and reinitiation reactions. [43,44] An one-pot preparation of Ni-initiators supported by bidentate ligands was attempted by Doubina et al Nickel cyclooctadiene (Ni(cod) 2 ) was reacted with aryl halides followed by the addition of one equivalent of a bidentate ligand (dppf, dppe, or dppp), or of two equivalents of the monodentate ligand PPh 3 (Scheme 3c). [71] The idea was to utilize the high reactivity of Ni(cod) 2 toward aryl halides combined with the lower binding ability of cod to nickel compared to bidentate phosphorous ligands.…”
Section: Ex Situ (External) Initiationmentioning
confidence: 99%
“…While it was already known that P3HT obtained via this method exhibits narrow polydispersities [26] and well-defined chain ends, [12,27] the discovery of the chain-growth mechanism marked a clear cut by providing new insight into the mechanism of the KCTP/GRIM method. Since then, many other welldefined CPs, including thiophene-, [25] fluorene-, [28,29] phenylene-, [30] and pyrrole-based [31] conjugated homopolymers, low bandgap homopolymers, [32,33] all-conjugated block copolymers, [28,31,34,[35][36][37][38][39][40][41] gradient copolymers, [42] and polymer brushes, [43][44][45][46][47][48][49][50] have been synthesized using KCTP. Several recent reviews further demonstrate the high activity in this field.…”
Section: Introductionmentioning
confidence: 99%
“…47,[70][71][72] Indeed, if this π-complexation is weak, the Ni-catalyst can easily dissociate from the growing polymer chain, hereby losing the controlled character. Therefore, whether the polymerization is actually living or not depends on the possibility of the catalytic Ni-moiety to 'travel' along the π-conjugated monomer, reach the terminal C-Br bond and oxidatively insert there within the lifetime that it remains complexed to the π-conjugated backbone.…”
Section: Homopolymerizationmentioning
confidence: 99%
“…[6] Kürzlich entwickelten wir die SIP von regioregulärem Poly(3-hexylthiophen) ausgehend von vernetztem Poly(4-bromstyrol) (PS(Br)), wobei wir die Vorzüge des Kettenwachstumsmechanismus der Kumada-Polykondensation nutzten. [7] Die palladiumkatalysierte Suzuki-Kupplungs-Polykondensation von Arylhalogeniden mit organischen Boranen ist eine weitere und bemerkenswert effiziente und vielseitige Route zu konjugierten Polymeren, die mit unterschiedlichen funktionellen Gruppen und Lösungsmitteln kompatibel ist. [8] Die klassische Variante der Suzuki-Polykondensation wird durch [Pd(PPh 3 ) 4 ] oder ähnliche Komplexe katalysiert und verläuft nach einem Stufenwachstumsmechanismus.…”
unclassified
“…Offensichtlich und im Unterschied zu unserer früheren SIP nach Kumada [7] erfolgt hier die Pfropfung nur in den äußersten Bereichen der PS(Br)-Schicht. Für kinetische Untersuchungen wurden je sechs Si-Wafer und Glasträger mit einer 2 nm dicken PS(Br)-Ankerschicht versehen.…”
unclassified